Inovação em serviços públicos: estudo de caso na secretaria municipal de saúde de Campina Grande - Gomes, Camilla Alves (2017)
Governments all around the world are always being pressured to suitably meet social demands that are increasingly more complex. The main challenge faced by the public sector consists of providing quality services with scarce resources and limited operational capacity. In Brazil, many are the problems faced by society, particularly the public health’s precarious condition, in a crisis situation. It is in this context that innovation has been a strategic factor to improve the quality of public services offered to citizens. This way, the main objective of this research is to analyze the factors that have influenced the innovation process of the services provided by Campina Grande’s Town Health Administration (Secretaria Municipal de Saúde de Campina Grande) is innovating in service providing. Specifically, the objective is to describe the innovations that took place; and to verify the conditioning factors that allowed them, as well as their barriers in the public sector. A case study was used as methodological approach. The data was collected via semi-structured interviews, direct observation, and document analysis. The data collected was treated via content analysis. The results showed that some actions taken by Campina Grande’s Town Health Administration can be classified as incremental innovations or innovations by recombination. Among the innovations by recombination are the Zika Virus Congenital Syndrome Specialized Ambulatory (Ambulatório Especializado em Síndrome Congênita do Vírus ZIKA), the CERAST, and the “Move, Campina” (“Mexe, Campina”) program. The incremental innovations include the decentralization of vesical probe exchange; the decentralized blood exam collection; and HyperDay at Home (HiperDia em Casa). Among the conditioning factors for the innovations executed by the Administration are the support of managers and leaders; staff training; crisis as an opportunity; public opinion; team effort; and knowledge and experiences exchange. Among the barriers to innovation the highlights are insufficient resources; laws and regulations; the economic crisis; political alternation; and strikes and socio-political barriers. Through the evidence, it was noticed that there are differences between the administrators’ and health service users’ perceptions that act as barriers and conditioning factors for innovation, apart from the preponderancy of Administrators’ Support and Professional Training as conditioning factors, as well as Insufficient Resources and Economic Crisis as barriers to innovation. As a research contribution, new conditioning factors were identified for those cited in the literature, such as knowledge and experiences exchange and the obstacles caused by constant strikes in the area. Besides, to the extent that the findings made possible a clearer comprehension of the characteristics the factors that influence the innovation process in the Heath Administration, there is an expectation that possible problems related to the barriers to be adjusted and for the innovation condition factors to be mobilized to achieve the proposed goals and improve public health services. Lastly, the results can also be useful for other instances of the public sector in developing actions aiming to innovate and help overcome obstacles in this process.